IMPLEMENTASI KEBIJAKAN VISI DAN MISI PEMBANGUNAN PERIODE PERTAMA PEMERINTAHAN KOTA TIDORE KEPULAUAN - Sudin, Idris (Jurnal Ilmiah Ecosystem, 2017)
The backround of vision policy implementation in this govermental development, was pushed by the duty of political elite leader for implementing their promise to societies through vision and mission presentation, so the power legitimation could be believed societies. This research explain about the implementation in developmental mission and vision Tidore Government during 2005-2010 years. More substansially, the aim that would be reached are to know the succes implementation model of George Edaward III, about communication, , resourch, bureaucratic structure and dissposition in making that vision and mission. Besides that, this thesis also want to study the policy implementation failure in Tidore developmental programe. The model that uses is Merille Gerindle model, foccused that an implementation is failure because two factors, namely: (1) it relates with the policy contents, (2) and, it relates with the public policy environment. Methode that used in this research is qualitative research model. The data analysis model, according to Miles Huberman in this research describing three analysis rank (1) data reduction, (2) data presentation, (3) Conclussion result. The research result showed that several field communication in implementing vision and mission like religion and indepence by selfregulating that exist or according with RPJMD developmental planning, , mass media, semiloka, form seminary, consolidation form, there is religion medium for civiz religious form. Resources are still lack, bureaucratic structural empowering is still weak. It insight by intervention behaviour and disfungtion between one part with the others.. Disposition is also still improved because low of commitmen, thrust, consistency in developmental implementation in Tidore Archipelago. Even the faile form policy implementation in order to make governmental programe indicates that policy makers and politital elite has big power to influence those implementation developmental programe implementation in Tidore Archipelago, because they determine the decission contents of those programes. The Reccomenadations mjust be improved in implemanting Governemntal developmental’s vision and mission is to communicate those vission and and at the really foccus. The improvement of human resources by practice and education wiyth step by step system for state apparatus in Tidore Government. Redesign of bureaucratic structure has aims in order to make open system and design management system toward simple of bureaucratic structure and make many function. People need ability improvement with commitmen, trust, consistency for doing government duty, with consider policy contents and policy environmental contex in the field area.